Bothrops Envenomation in Dogs: Local and Systemic Manifestations: - Machado, Mizael; Vieira de Paula, Larissa; Henrique Marques Araújo, Gustavo; Rêgo Queiroz, Cintia Regina; Meziara Wilson , Tais; Botelho de Castro , Márcio (Acta Scientiae Veterinariae, 2022)
Background: Snakebite envenoming is a condition that affects humans and domestic animals worldwide. Identification of the snake species involved in the envenomation is infrequent. Bothrops envenomation presents typical clinicopathological features. This report describes epidemiological, clinical, and pathological data of 2 cases of Bothrops envenomation in dogs, including the first case of Bothrops moojeni snake striking a domestic animal in Brazil. Cases: Case 1. A dog was witnessed to have a Bothrops moojeni snakebite on a farm. In the first 24 h, acute lameness, pain, diffuse swelling, focal bleeding at the left forelimb, and increased whole-blood clotting time were observed in the envenomed dog. Polyvalent antivenom was administered in addition to fluid therapy, analgesics, corticosteroids, and antibiotics. On the 15th day, the animal presented spontaneous bleeding at the wound site, thrombocytopenia, and increased whole-blood clotting time. An additional dose of polyvalent antivenom was administered, and local treatment at the snakebite site was initiated. After 13 days, the dog showed no clinical or laboratory changes and recovered entirely. Case 2. A mongrel dog was taken for a necropsy to determine the cause of death. Grossly, major findings included swelling in the nasal plane that extended to the neck and dissecting hemorrhage in the subcutaneous tissue and adjacent musculature. Hemorrhages were observed in the heart, parietal pleura, left forelimb, lumbar region, and perirenal tissue. Marked necrosis and disruption of small blood vessels and lymphatics within the deep dermis and subcutaneous tissue were the main microscopic findings close to the snakebite site. Additionally, degeneration and necrosis of muscle fibers and dissecting hemorrhage were observed in the head and neck tissues surrounding the snakebite site. Kidneys showed marked interstitial hemorrhage and acute tubular nephrosis. Discussion: Bothrops envenoming is characterized by local (hemorrhage, dermonecrosis, and myonecrosis) and systemic (coagulative disorders, systemic hemorrhage, and acute kidney injury) changes due to the effect of the main venom components such as phospholipase A2 and metalloproteinases. These changes are hallmarks for the bothropic envenomation, supporting the diagnosis in cases 1 and 2. In case 1, the dog developed a Bothrops moojeni snakebite envenomation, but the immediate treatment with antivenom allowed a favorable outcome. In case 2, gross and microscopic findings supported the presumptive diagnosis of fatal bothropic envenomation. A marked local reaction such as swelling, pain, bleeding, bruising, and tissue necrosis was observed in case 1. In case 2, the most significant local changes were swelling and edema at the head and neck, hemorrhage in the subcutaneous tissue, and adjacent musculature. Systemic effects were observed clinically as spontaneous bleeding, thrombocytopenia, increased whole-blood clotting time (Case 1), systemic hemorrhages, and acute tubular nephrosis (Case 2). A proper treatment probably prevented the development of acute renal failure in Case 1. Herein, we show the first case of accidental snakebite envenomation by B. moojeni in a dog in Brazil. Information is scarce on the identification of venomous snake species striking domestic animals. Fast detection of well-determined clinical and pathological findings of Bothrops envenomation is essential for a correct diagnosis, therapeutics, and a good prognosis, even in cases with an unknown history. Keywords: Bothrops moojeni, venomous, coagulative disorders, canine, snake, snakebite.